Implementasi Konsep Arsitektur Kontemporer: Re-Desain Kampus Fakultas Teknik Universitas Subang - Rosyadi, Rosyid; Barliana, Muhammad Syaom (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2023)
Subang University is one of the higher education institutions that has a vision to become a Developing and leading Higher Education at the West Java level in 2020. In general, the problems of campus building infrastructure at Subang University are: how to produce concepts and implementations of campus buildings that are in accordance with the needs of teaching and learning activities; guarantee the development of specific superior campus building infrastructure based on comparative and competitive advantages; achieve and improve the quality according to the target and the relevance of the contents of campus building infrastructure for the people of Subang. The purpose of implementing the concept of Contemporary Architecture on Campus Development of the Faculty of Engineering, Subang University, is expected to support and accommodate Teaching and Learning Activities at the Faculty of Engineering Unsub. The research method used in the Re-Design Study of the Faculty of Engineering, Subang University is a qualitative descriptive method with direct observation in the field, documentation, literature study, interview techniques with related resource persons. The application of contemporary architectural concepts at the Faculty of Engineering, Subang University is taken from several points contained in the characteristics of contemporary architecture, namely: (i) ideology; (ii) Styles; (iii) Strong geometric shape design ideas. Contemporary principles include articulation is the body part of the building that will clarify the 'servant' and 'served' spaces or floors; The space must be inviting to use; Harmony between materials, forms and manufacturing processes.Keywords: Concept implementation, Contemporary architecture, University of Subang